Analisis Pengaruh Jumlah Pengangguran Terhadap Tingkat Kemiskinan Menggunakan Metode Regresi Linear Sederhana - Fransisco Julius Marpaung; Johan Siregar; Crisvan Simamora; Gilbert Surbakti; Valdiona Ginting; Indra M. Sarkis S. (Universitas Methodist Indonesia, 2024)
Unemployment and poverty are problems that many people in the region experience, one of which is the city of Medan. Unemployment is one of the main causes of poverty in the community because there are not enough jobs to meet the needs of life. This study aims to analyze the influence of the unemployed on the poverty rate in Medan City using a simple linear regression method. The data came from the Central Statistics Agency of Medan City during the last five years. The analysis results showed a positive relationship between the number of unemployed and the poverty rate, with the regression coefficient showing that every 1% increase in the unemployment rate would increase the poverty rate by 1,147,853,639. The analysis results using the simple linear regression method show that the value of a= constant is 176,1392505, which means that if there is no unemployment (X), the poverty number (Y) is 176,139250. As for the b = regression coefficient, the value is 1,147853639. This means that by adding 1% to the unemployment rate (X), the number of people living in poverty (Y) will increase by 1,147853639. This research is expected to contribute to designing effective policies to reduce unemployment and poverty in Medan City.